A construção do juiz das garantias no Brasil: a superação da tradição inquisitória - Larissa Marila Serrano da Silva (2012)
The present study explores the elements that highlight the contours of the new figure of the judge of guarantees provided for in the Bill of Reform of the Code of Criminal Procedure. To this end, the role of the judge in the preliminary investigation stage along the trajectory of the Brazilian criminal process is investigated. Such research allows for the identification of the legal and cultural heritage bequeathed to the traditional figure of the judge as inquisitor, present in almost four centuries of our history. Aware of such tradition, the study aimed toovercome the accusatory influence and to guide the construction of the new investigation judge, understood as guarantor of the fundamental rights, bound to the assumptions of the accusatory constitutional model. It also aimed at examining the ideological basis of the new figure which is, to a large extent, inserted in the legislations of European and Latin American countries, who have left the judge of instruction and have instituted a similar figure to the one presented by the Bill of reform. Finally, the thesis evaluates the Brazilian proposal and confronts the main theoretical arguments in favor and against the deployment of this new character in the procedural scenario of the homeland.